2022
DOI: 10.3389/fpsyg.2022.924492
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Among Green Human Resource Management, Green Knowledge Sharing, Green Commitment, and Green Behavior: A Moderated Mediation Model

Abstract: This study aims to examine the underlying mechanism of the relationship between perceived green human resource management (GHRM) and perceived employee green behavior (EGB). By drawing on attitude and social exchange theories, we examined green commitment (GC) as a mediator and green knowledge sharing (GKS) as a moderator of the GHRM–EGB relationship. The study employs partial least square structural equation modeling (PLS-SEM) to analyze 329 responses. Data were collected in two time lags. The empirical resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 84 publications
1
7
0
Order By: Relevance
“…Finally, the present research found that workers' green knowledge-sharing behavior at the workplace considerably moderates the relationship between green HRM and an organization's commitment to sustainability (H3). This finding concurs with what has been discovered in the past, such as by Khan et al . (2022), who uncovered a significant moderating role of green knowledge sharing in the relation of green HRM and an organization's green commitment to achieve sustainability.…”
Section: Discussionsupporting
confidence: 94%
“…Finally, the present research found that workers' green knowledge-sharing behavior at the workplace considerably moderates the relationship between green HRM and an organization's commitment to sustainability (H3). This finding concurs with what has been discovered in the past, such as by Khan et al . (2022), who uncovered a significant moderating role of green knowledge sharing in the relation of green HRM and an organization's green commitment to achieve sustainability.…”
Section: Discussionsupporting
confidence: 94%
“…Hence, embracing GHRM practices has become a critic strategy for those companies wherein human resources play an active part in becoming environmentally sensitive (Adriana et al, 2020 ). In relation to that, GHRM can nurture supporters across employees that are willing to contribute to environment (Khan et al, 2022 ). In this study, we assumed that being in an environment-friendly atmosphere caused by GHRM will create positive attitudes on the part of employees nourishing their sense of ownership, which will mediate the relationship between GHRM and employees' work engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been observed that GHRM are predictors of innovation outcomes in the organization [21]. Implementing GHRM to green innovative work behavior is based on behavior devoted toward green ideas generation, promotion, and realization [22]. On the relationship between GHRM and GIWB, it can be argued that GHRM can positively contribute to GIWB for the following reasons.…”
Section: E Research Hypothesismentioning
confidence: 99%
“…Green innovative work behavior partially mediates the relationship between green human resources management and business model innovation GHRM perceives as supportive HR practices that enhance the culture of shared knowledge to improve employee's performance [24]. GHRM enables employees to build a wellorganized and effective environment to acquire, assimilate, and share their knowledge that leads to employee green behavior [22]. Scholars have mentioned about the role of knowledge sharing in affecting business model innovation to be more effective and feasible [4].…”
Section: E Research Hypothesismentioning
confidence: 99%